2016
DOI: 10.20882/adicciones.890
|View full text |Cite
|
Sign up to set email alerts
|

Adolescentes con Trastorno por juego en Internet (IGD): perfiles y respuesta al tratamiento

Abstract: Demand for treatment for problems related to the use of video games have increased significantly in adolescents. Most cases have a comorbid mental disorder that jeopardises both pathologies. The aim of this study is to describe profiles of adolescents with Internet Gaming Disorder (IGD) according to comorbidity and analyze treatment response at 3 and 6 months. A sample of 86 patients which consulted in the Addictive Behavior Unit of a hospital was assessed with diagnostic criteria for IGD, the interview K-SADS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
28
0
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 25 publications
7
28
0
12
Order By: Relevance
“…This same study found that 6.5% were "engaged gamers at high risk", and 11.9% were "engaged gamers at low risk", with the remainder classified as "regular" or "casual" gamers. In a clinical sample of 86 disordered adolescent gamers, it was found that 96.6% were male [38].…”
Section: Introductionmentioning
confidence: 96%
“…This same study found that 6.5% were "engaged gamers at high risk", and 11.9% were "engaged gamers at low risk", with the remainder classified as "regular" or "casual" gamers. In a clinical sample of 86 disordered adolescent gamers, it was found that 96.6% were male [38].…”
Section: Introductionmentioning
confidence: 96%
“…De momento, el acuerdo es prácticamente unánime respecto de la consideración del TJA como una adicción comportamental (Leeman y Potenza, 2012;Petry, 2010); dicho consenso no se ha alcanzado respecto de otras supuestas adicciones comportamentales (Chacón-Cuberos et al, 2018;Martín-Fernández et al, 2017). No obstante, también hay evidencia de un alto nivel de variabilidad individual entre pacientes con TJA (Albein-Urios, Martinez-González, Lozano, Clark y Verdejo-García, 2012; Blaszczynski y Nower, 2002; Steward et al, 2017), que probablemente determine las respuestas diferenciales al tratamiento (Aragay et al, 2015;Chu y Clark, 2015;Melville et al, 2007).…”
unclassified
“…No obstante, los índices de prevalencia más plausibles encontrados para otros PARs no relacionados con drogas, también muestran porcentajes considerables de conductas adictivas potencialmente clínicas entre universitarios. Esto apoya la relevancia del reconocimiento e intervención tempranos, sobre todo porque las personas que realizan comportamientos adictivos a menudo experimentan síntomas psicopatológicos comórbidos e incluso ideación suicida (Bousoño et al, 2017;Martín-Fernández et al, 2017). Evaluar correctamente los perfiles individuales de comportamientos problemáticos potencialmente clínicos, como los PARs no relacionados con drogas y los patrones de práctica de AFO, ayuda a identificar a las personas en riesgo, contribuye a la prevención, y ayuda a establecer planes de tratamiento adaptados al perfil de una persona (Martín-Fernández et al, 2017).…”
Section: Fortalezas Y Limitacionesunclassified